Judging without Impunity: On the Criminal Responsibility of Authoritarian Judges - Graver, Hans Petter (Bergen Journal of Criminal Law & Criminal Justice, 2016)
The purpose of this article is to examine how far, with due respect for the rule of law, criminal sanctions could be applied to judges for the exercise of their judicial functions. The main focus is on judges in authoritarian regimes, situations where judges are employed by the holders of power in the realisation of political oppression. The article presents the normative basis for holding judges accountable in some different examples of national laws, and looks into the few historical examples of judges that have been held accountable under criminal law. The article concludes that there exists a core of justice, present in the minds of ‘all civilized people’, and that to this core belong substantial and manifest human rights violations, intolerable disproportionate punishments and substantial violations of the right to a fair trial. Judges who disregard this core of justice may be held accountable for their judicial rulings, even when this formally entails applying laws retroactively. Criminal guilt can be established by the objective facts, together with the fact that no judge can claim with credibility that he was unaware of doing something wrong. A positive basis for this approach may be found in the statutes of the International Criminal Court.